Polymorphic variation in CYP19 and the risk of breast cancer - Baxter, S.W.; Choong, D.Y.H.; Eccles, D.M.; Campbell, I.G. (Carcinogenesis (New York), 2001)
The production of estrogen from androgen via the estrogen biosynthesis pathway is catalyzed by aromatase P450 (cyp19). We have assessed the frequency of allelic variants of the CYP19 intron 4 [TTTA]n repeat in 327 breast cancer cases and 253 controls from southern England. Previous studies have suggested that the [TTTA]10 repeat and [TTTA]12 repeat variants represent low penetrance breast cancer susceptibility alleles. Compared with controls our breast cancer cases had a statistically significant positive association with the [TTTA]10 allele (1.5 versus 0.2%, P = 0.028) and the [TTTA]8 allele (13.5 versus 8.7%, P = 0.012). The frequency of the [TTTA]12 allele was not significantly elevated in our study group compared with controls (2.3 versus 2.2%, P = 1.00). The CYP19 intron 4 [TTTA]n repeat is unlikely to have a functional effect on aromatase activity and it is more likely that the [TTTA]8 and [TTTA]10 variants are in linkage disequilibrium with other functional CYP19 variants.